Linking rooftop farms, urban regeneration and sustainable housing in Berea, Johannesburg: the case of the urban agriculture initiative at Coronia gardens - Shapurjee, Yasmin (My University, 2022)
Rooftop farms serve multiple functions in cities and are increasingly acknowledged as potential drivers for sustainable development. This research explores the relationships between rooftop farms, urban regeneration and sustainable housing in Berea, Johannesburg, using a qualitative case study of the Urban Agriculture Initiative rooftop farm at Coronia Gardens. In-depth interviews were conducted with a sample of project partners, urban farmers and residents. Findings indicate how rooftop farming aligns with certain urban regeneration goals, providing benefits including employment creation, skills development, land use efficiency, and social capital for farmers. However, resident benefits have not been realised. Challenges include limited involvement and engagement in the rooftop farm, low awareness levels, a lack of food crop diversity, and a disconnect between rooftop farms and ground-level activities. Greater integration between various inner-city urban agriculture projects is recommended, along with strategies to include rooftop farms in existing and planned affordable inner-city housing developments across Johannesburg.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Urban Studies to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, 2022